Integrasi Matematika dan Islam: Logika Matematika dalam Al-Qur'an - Alghar, Muhammad Zia; Afandi, Muhammad Irfan (Program Pascasarjana UNU Surakarta, 2024)
One of the goals of national education is to form students who are faithful and devoted to God Almighty. Islamic-integrated mathematics learning is a bridge to achieving this goal. This study aims to explore the verses in the Quran related to the concept of mathematical logic. A literature review using qualitative research was conducted in this research. Data were obtained from the Quran, the Book of Tafsir, and relevant journal articles. The results showed the concept of mathematical logic in the Quranic verses. The conjunction form is found in surah Al-Baqarah verse 25, the disjunction form is found in surah Al-Balad verses 12 to 16, and the negation form is found in surah Al-Kafirun verses 2 to 5. Implication form is found in surah Al-Fatihah verses 6 and 7. The results of this study can be a reference for learning resources in mathematical logic and logic and set integrated with Islam at the school and lecture levels.